Forecasting the Development of Islamic Bank in Indonesia: Adopting ARIMA Model - Syarif, Ahmad (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
Financial activities that are often carried out by people in developed and developing countries. Banks can collect public funds directly from customers, then distribute them to the public. Islamic banks still have a good reputation in the community so that the assets and third party funds of Islamic commercial banks grow. This is also reinforced by public optimism due to regulation of Banking Synergy in One Ownership for the development of Islamic Banking. The purpose of this study is to forecast the growth of Islamic banking after the implementation of banking synergy regulations in one ownership as an effort to increase the efficiency of the Islamic banking industry. This study used the secondary data all of  the Islamic Banks in Indonesia from Financial Service Authority by Autoregressive Integrated Moving Average (ARIMA) period 2015-2019 as the estimated data and 2020-2022 as the forecasting data in quarter. This study used two variables, asset and third-party fund, to estimate the best model. The result shows ARIMA (0,1,1) has the small AIC and significant value as best estimation model. The growth of Islamic banks in 2020 will increase by 7.4 % in assets and 7.3 % by the end of 2022 to IDR 437 trillion. Meanwhile, third party funds by the end of 2022 will increase by 8 % with total third party funds of IDR 361 trillion. Banking Synergy in One Ownership Order has the potential to increase the effectiveness and the efficiency of the Islamic Banking Industry at future.